Country-specific determinants of horizontal and vertical intra-industry agri-food trade of the Visegrad Countries - Attila Jambor (FIW - Research Centre International Economics, 2013)
The article analyses patterns and country-specific determinants of Visegrad Countries' (VC) agri-food trade with the European Union. Literature focusing on the country-specific determinants of vertical and horizontal intra-industry trade is rather limited and those analysing agricultural (or agri-food) trade are extremely rare. Therefore, the paper seeks to contribute to the literature by covering latest theory and data available on the topic to provide up to date results and suggestions. Moreover, it seeks to identify the determinants of horizontal and vertical intra-industry trade of the Visegrad Countries after EU accession. Results suggest that agri-food trade of the Visegrad Countries is mainly inter-industry in nature but intra-industry trade is dominated by vertical elements. Results verify that determinants of horizontal and vertical IIT differ and suggest that economic size is positively, while distance is negatively related to both sides of IIT. However, the relationship between vertical IIT and differences in factor endowments as well as FDI is ambiguous.
Keywords: F14; 330; Visegrad Countries; intra-industry trade; determinants